Konstruksi Literasi Bahasa Indonesia dalam Mengembangkan Kemampuan Berpikir Kritis Mahasiswa - Rahmadan, Rizki; Aripin, Samsul; Aisyah, Siti Nur; Hermiati, Hermiati; Anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyse the role of Indonesian language literacy in improving the critical thinking skills of students in economics study programmes. The study was conducted using a qualitative descriptive approach through literature review and analysis of learning documents related to the development of literacy and critical thinking skills. The data were analysed by examining the relationship between Indonesian language literacy practices, learning strategies, and the academic context in which the learning process took place. The results of the study indicate that Indonesian language literacy plays an important role in shaping students' critical thinking skills. Literacy not only functions as a means of scientific communication, but also as a foundation for building analytical thinking through activities such as reflective writing, academic discussions, and economic text analysis. The use of digital technology, such as writing applications and online discussion forums, supports this process by providing a wider space for interaction and information processing. In addition, lecturer support in integrating literacy with critical learning approaches and a conducive academic environment also strengthens the development of students' critical thinking skills. These findings emphasise that strengthening Indonesian language literacy needs to be an integral part of the education process in the field of economics in order to produce graduates who are communicative, analytical, and able to respond to global developments